Shedding of methicillin-resistant Staphylococcus aureus by colonized patients during procedures and patient care activities. (19th February 2019) - Alhmidi, Heba; Cadnum, Jennifer L.; Koganti, Sreelatha; Jencson, Annette L.; Rutter, Joseph D.; Bonomo, Robert A.; Wilson, Brigid M.; Mayer, JeanMarie; Samore, Matthew H.; Donskey, Curtis J.
Abstract: Objective: Medical procedures and patient care activities may facilitate environmental dissemination of healthcare-associated pathogens such as methicillin-resistant Staphylococcus aureus (MRSA). Design: Observational cohort study of MRSA-colonized patients to determine the frequency of and risk factors for environmental shedding of MRSA during procedures and care activities in carriers with positive nares and/or wound cultures. Bivariate analyses were performed to identify factors associated with environmental shedding. Setting: A Veterans Affairs hospital. Participants: This study included 75 patients in contact precautions for MRSA colonization or infection. Results: Of 75 patients in contact precautions for MRSA, 55 (73%) had MRSA in nares and/or wounds and 25 (33%) had positive skin cultures. For the 52 patients with MRSA in nares and/or wounds and at least 1 observed procedure, environmental shedding of MRSA occurred more frequently during procedures and care activities than in the absence of a procedure (59 of 138, 43% vs 8 of 83, 10%; P < .001). During procedures, increased shedding occurred ≤0.9 m versus >0.9 m from the patient (52 of 138, 38% vs 25 of 138, 18%; P = .0004). Contamination occurred frequently on surfaces touched by personnel (12 of 38, 32%) and on portable equipment used for procedures (25 of 101, 25%). By bivariate analysis, the presence of a wound with MRSA was associated with shedding (17 of 29, 59% versus 6 of 23, 26%; P = .04). Conclusions: Environmental shedding of MRSA occurs frequently during medical procedures and patient care activities. There is a need for effective strategies to disinfect surfaces and equipment after procedures.